Internal Noise for Choosing Items is Affected by Their Number and Spatial Arrangement - B A S Hasan (i-Perception, 2011)
We studied whether, when choosing an item out of n items, the internal noise associated with making this choice is affected by the number of items and/or their spatial arrangement. Each item is represented by a patch of Gabor segments with different orientations; the task is to identify the patch with vertical orientation. The patches are positioned around the clock, and some spatial jitter is applied to each patch. We found an increase in internal noise with the number of patches. Jitter causes higher internal noise compared with no jitter, but different jitter configurations do not affect internal noise.